Pelatihan Pembuatan Games Edukatif Menggunakan Educandy bagi Guru Sekolah Dasar Kecamatan Kerinci Kanan Kabupaten Siak - Syafriafdi, Non; Suarman; Oktary, Dian; Yakub, Elni; Puspita, Dina; Pernandes, Putri Chaya (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2025)
This service activity aims to enable participants to create educational games using candy for elementary school teachers in Kerinci Kanan subdistrict, Siak district. The methods for implementing service activities are lectures, demonstrations and exercises in making educational games using Educandy. The targets of this training activity in making educational games using Educandy are elementary school teachers in Kerinci Kanan District. Systematic activity plans (a) elementary school teachers understand the concept of educational games using candy, (b) practice making educational games using candy. (c) Discussion and questions and answers to discuss and explain things that participants do not understand as feedback for resource persons.